2015
DOI: 10.1161/circimaging.114.002546
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Enlargement Is Associated With Right Ventricular Dysfunction and Loss of Blood Volume in Small Pulmonary Vessels in Chronic Obstructive Pulmonary Disease

Abstract: Background COPD causes significant morbidity and concomitant pulmonary vascular disease and cardiac dysfunction are associated with poor prognosis. CT-detected relative pulmonary artery enlargement defined as a pulmonary artery to ascending aorta diameter ratio greater than one (PA:A>1) is a marker for pulmonary hypertension and predicts COPD exacerbations. However, little is known about the relationship between the PA:A ratio, pulmonary blood volume, and cardiac function. Methods and Results A single-center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 40 publications
7
61
0
3
Order By: Relevance
“…In addition, these acute changes could be exaggerated by centralization of blood flow, similar to what we have observed in the stable state of COPD. 23,30 We also observed that younger age was associated with pulmonary arterial enlargement at the time of admission. The mechanism for this phenomenon is unknown and requires further study, although it could be due to impaired vascular distensibility in older patients.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In addition, these acute changes could be exaggerated by centralization of blood flow, similar to what we have observed in the stable state of COPD. 23,30 We also observed that younger age was associated with pulmonary arterial enlargement at the time of admission. The mechanism for this phenomenon is unknown and requires further study, although it could be due to impaired vascular distensibility in older patients.…”
Section: Discussionsupporting
confidence: 53%
“…A single blinded reviewer measured the pulmonary arterial diameters in the tubular portion of the main pulmonary artery at the level of its bifurcation and the mean of two perpendicular measurements of the ascending aorta to represent the aortic diameter, as previously reported (Fig 2). 17,18,23 The median time between baseline and AECOPD scans was 99 days (range, 7-352 days) and 103 days (range, 35-299 days) between AECOPD and follow-up imaging. Reviewers of the CT scans were blinded to all other clinical data.…”
Section: Review Of Imagingmentioning
confidence: 99%
“…However, mild-to-moderate PH in COPD is commonly thought to be caused by the destruction of small pulmonary vessels as a consequence of emphysema, or secondary to vasoconstriction in response to hypoxia. To support these hypotheses, mild-to-moderate PH in COPD has been consistently reported to be related with a reduction of small vessel areas16 or volume38 at CT examination. Our study is the first to report in vivo data on the distal vascular bed in patients with COPD with severe PH.…”
Section: Discussionmentioning
confidence: 95%
“…In the literature evaluation of %CSAs values in COPD subjects with PH was significantly negatively correlated, as in our population of COPD without severe PH. This result was ascribed to reduced distensibility of small vessels, hypoxic vasoconstriction and vessel destruction secondary to emphysema 16 38. However, this study was performed based on a population of COPD subjects with severe emphysema, as assessed by a visual of percentage of emphysema on CT scans superior to 75%,7 16 and corresponding to total automatic quantification (LAA%) of 25%, and in which the degree of mPAP elevation did not exceed the threshold of severe PH.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was performed using CAAS MRV 3.4 (Pie Medical Imaging, the Netherlands). Assessments of ventricular mass, volumes, and function were then obtained, as previously described 15, 16. RV‐PA coupling was assessed by a ratio of RV end‐systolic elastance (Ees)/arterial elastance (Ea) that was estimated by “volume” method (Ees/Ea=RV stroke volume/end systolic volume) 17, 18.…”
Section: Methodsmentioning
confidence: 99%